PENGARUH KEMAMPUAN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI - Indra Drajat (Jurnal Dinamika Manajemen, 2014)
The research purpose is to examine the effect of work ability and organizational cilmate toward employee performance. Sample is the employee that consist of 99 units which chosen with stratified random sampling techniques. The results shows that work ability and organizational climate is simultaneously effect positively employess performance with determination is 80,1%. Partially, work ability and organizational climate influece significantly. Otherwise, the two variables that have more dominant influence is work ability. In order to increase employee performance, work ability should be increased through training that fit to organizational needs. Furthermore, it is needed to increase intrapersonall relationship to build better organizational climate. Key Words.      DPUKBT, workability, organizational climate, and employee performance